2013
DOI: 10.1021/es301229m
|View full text |Cite
|
Sign up to set email alerts
|

Chrysotile Dissolution in the Rhizosphere of the Nickel Hyperaccumulator Leptoplax emarginata

Abstract: Ni phytoextraction processes need further understanding of the interactions between Ni availability in soils and its absorption by plant roots. The large metal uptake and root exudation by hyperaccumulator species could accelerate the weathering process of Ni-bearing phases in the rhizosphere. The aim of this work was to quantify the weathering of a Ni-bearing mineral phase in the rhizosphere of the Ni-hyperaccumulator Leptoplax emarginata. The studied mineral was chrysotile which was characterized by a low Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Chelator-based extractants based on synthetic amino-polycarboxylic acids include EDTA and DTPA. The DTPA (Diethylene triamine pentaacetic acid) method was originally developed to diagnose deficiency of micronutrients in soils (Lindsay and Norvell, 1978), but has been widely used for studies with ultramafic soils (L'Huillier and Edighoffer, 1996;Echevarria et al, 1998Echevarria et al, , 2006Lazarus et al, 2011;Chardot-Jacques et al, 2013;Ünver et al, 2013). The DTPA-extract is made up of 0.005 M DTPA with 0.01 M CaCl 2 and is buffered at pH 7.3 with 0.01 M triethanolamine (TEA).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Chelator-based extractants based on synthetic amino-polycarboxylic acids include EDTA and DTPA. The DTPA (Diethylene triamine pentaacetic acid) method was originally developed to diagnose deficiency of micronutrients in soils (Lindsay and Norvell, 1978), but has been widely used for studies with ultramafic soils (L'Huillier and Edighoffer, 1996;Echevarria et al, 1998Echevarria et al, , 2006Lazarus et al, 2011;Chardot-Jacques et al, 2013;Ünver et al, 2013). The DTPA-extract is made up of 0.005 M DTPA with 0.01 M CaCl 2 and is buffered at pH 7.3 with 0.01 M triethanolamine (TEA).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Experiments have shown that the chelating activity of exudates from some fungi and lichen (which has a fungal component) modify the chemical composition of chrysotile fibres in vitro, affecting their chemical reactivity and structure and potentially altering toxicity. These organism-driven weathering processes can reduce chrysotile fibre toxicity (Daghino et al, 2006(Daghino et al, , 2009, and accordingly increase iron (Fe), magnesium (Mg) and nickel (Ni) concentrations in surrounding substrates (Chardot-Jacques et al, 2013). These dissolved elements could provide plant nutrition but can also be lost though leachate (Chardot-Jacques et al, 2013).…”
Section: Bioweatheringmentioning
confidence: 99%
“…These organism-driven weathering processes can reduce chrysotile fibre toxicity (Daghino et al, 2006(Daghino et al, , 2009, and accordingly increase iron (Fe), magnesium (Mg) and nickel (Ni) concentrations in surrounding substrates (Chardot-Jacques et al, 2013). These dissolved elements could provide plant nutrition but can also be lost though leachate (Chardot-Jacques et al, 2013). In one experimental study, the iron released was not incorporated into the fungal biomass (Daghino et al, 2008), but the fungi's progressive removal of reactive iron ions, which are responsible for asbestos's DNA damage, was encouraging (Daghino et al, 2006).…”
Section: Bioweatheringmentioning
confidence: 99%
“…However, it is evident that plants secrete organic acids or amino acids intended for the chelation of metallic elements (Briat and Lebrun, 1999;Puschenreiter et al, 2003;Wenzel et al, 2003). Some hyperaccumulators may also enhance mineral dissolution to improve their Ni uptake (Chardot-Jacques et al, 2013). This contribution modified the soil edaphic conditions and may increase the bioavailable Ni content and consequently may potentially modify its Ni isotopic signature.…”
Section: Implications For the Ni Cycle In Surface Soilsmentioning
confidence: 99%